Clinical benefits and adverse effects of siwak (S. persica) use on periodontal health: a scoping review of literature - Haslinda Ramli; Tuti Ningseh Mohd-Dom; Shahida Mohd-Said (BMC, 2021)
Abstract Background Siwak is a chewing stick used as an oral hygiene aid associated with Muslim communities across the globe since more than 1500 years ago. Used either exclusively or in conjunction with a regular toothbrush, there is evidence supporting its clinical effectiveness in plaque control, but adverse effects on periodontal health remains inconclusive. Objective This study aims to systematically review the wide range of data and literatures related to siwak practice and its effect on periodontal health. Method The review was conducted based on scoping review techniques, searching literature in EBSCOHOST, PubMed, SCOPUS and Google scholar databases using the following search terms: "siwak' or 'miswak' or 'chewing stick" for intervention, and "periodontium or 'periodontal' or 'periodontal health' or 'periodontal disease" for outcome. Articles published between January 1990 to March 2021 and written in English language were included. Results A total of 721 articles collected from the search and 21 of them were eligible for the final analysis. Results of this study was described based on clinical and antibacterial reporting of siwak, method of siwak practice and its adverse effect on oral health. Siwak was found effective at removing dental plaque and improving periodontal health over time although its effect on subgingival microbiota was inconclusive. Presence of gingival recession and clinical attachment loss were much more commonly reported in siwak users, attributable to variations in the methods employed for tooth cleaning using the siwak. Conclusion There is substantial evidence that the lack of standardised reporting for effective siwak use may have resulted in contradictory findings about its oral hygiene benefits and adverse effects. As such, future work on safe and effective siwak practice is to be advocated among its users.